2021
DOI: 10.3389/fneur.2021.637932
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Rituximab on Neuromyelitis Optica-Associated Optic Neuritis

Abstract: Purpose: To prospectively investigate the efficacy and tolerance of low-dose rituximab (RTX) for the treatment of neuromyelitis optica-associated optic neuritis (NMO-ON).Methods: Optic Neuritis patients with seropositive aquaporin 4-antibody (AQP4-Ab) were diagnosed with NMO-ON and recruited for treatment with low-dose RTX (100 mg * 4 infusions) and were then followed monthly for a minimum of 3 months. Reinfusion of 100 mg RTX was given when the CD19+ B lymphocyte frequency was elevated to above 1%. The serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…RTX reinfusions were administered whenever B cells were repopulated, even though the dosage of RTX varied from one to another (13,18,20,33,34). Greenberg et al (22) compared the time to B-cell repopulation (defined as a CD19 percentage of 2% or greater) after different RTX doses and found that 1000 mg per dose yielded more prolonged B-cell depletion than 100 mg per dose (184 ± 72 days versus 99 ± 36 days), which may provide support to more frequent reinfusion when low RTX dosing strategies were applied (13,27,28,35,36). Although the association of clinical relapses with B-cell repopulation has been well determined to date, it is of note that we have observed that many patients with B-cell repopulation maintained a long-term relapse-free condition in real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…RTX reinfusions were administered whenever B cells were repopulated, even though the dosage of RTX varied from one to another (13,18,20,33,34). Greenberg et al (22) compared the time to B-cell repopulation (defined as a CD19 percentage of 2% or greater) after different RTX doses and found that 1000 mg per dose yielded more prolonged B-cell depletion than 100 mg per dose (184 ± 72 days versus 99 ± 36 days), which may provide support to more frequent reinfusion when low RTX dosing strategies were applied (13,27,28,35,36). Although the association of clinical relapses with B-cell repopulation has been well determined to date, it is of note that we have observed that many patients with B-cell repopulation maintained a long-term relapse-free condition in real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies took the proportion of CD19 + B lymphocytes in total lymphocyte counts greater than 1% as the indication of reinfusion, and some took worsenings as the indication of reinfusion [16]. Additionally, the percentage of CD19- or CD20-positive B cells of total lymphocytes >1% was regarded as repopulation [13, 14]. CD20 + B cells-guided RTX strategy prolongs the therapy interval and reduces other immunomodulatory drugs usage including immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, most studies chose a small dose scheme with the average dose ranged from 100 to 600 mg, and most worsenings correlated with an increase of CD20 + B cells [6,12]. Very low-dose RTX (100 mg) has also been used in other immune-mediated neurological diseases, such as neuromyelitis optica spectrum diseases, either in induction treatment or maintenance treatment [13][14][15]. In the current study, 5 patients were treated with a very low dose of RTX.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects of treatment include possible infusion reaction, opportunistic infections, and delayed leukopenia. Alternatives include low dose rituximab, which is also efficient and well-tolerated in the treatment of NMOSD, with significant decrease in anti-AQP4 antibody concentration after induction treatment and a relapse-free rate of 92.3% in 43 patients followed-up over 12 months 78 . In addition, it is more convenient with a less frequent dosing compared to oral immunosuppressants that need to be taken daily.…”
Section: Discussionmentioning
confidence: 99%